The Syntax And Semantics Of Gã Future Markers - Campbell, A. (Acta Linguistica Hafniensia, 2022)
This paper explores the syntax and semantics of two grammatical markers of future time in Gã (Niger-Congo, Kwa): bàá- and àá-. The coexistence of àá- and over a long period, coupled with their overlapping roles, has led to some inconsistency in their analysis. I show that in modern Gã, bàá- is the most prevalent future marker, with àá- existing much less prominently alongside it. Data from natural speech and elicitation reveal that both markers have modal functions in addition to the temporal function. Bàá can also be used specifically to mark habits. Due largely to the overwhelming frequency of the temporal function in the discourse data, I maintain that the primary function of bàá- is as a future tense marker. It is therefore not purely modal. àá- has all but fallen out of use and has a more modal than temporal function. This study uncovers previously unreported non-temporal uses of bàá- and underscores the crucial role played by frequency in the determination of category function.
Research Article
Keywords: tense; future; modal